MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA PENGAJARAN GURU SMP NEGERI 1 SUNGGAL - Feronika Rismaida; Akrim Akrim; Faisal Rahman Dongoran (EDUTECH, 2023)
This research is a qualitative research in the form of a case study. This research was conducted at SMP Negeri 1 Sunggal in Deli Serdang Regency. The purpose of this study was to find out how the principal's management improves teacher teaching performance at SMP Negeri 1 Sunggal District. The respondents of this study were school principals, vice principals, teachers and students. Data collection techniques by observation, interviews and documents. The results of this study are that SMP Negeri 1 Sunggal has implemented policies quite well to improve teacher teaching performance and is trying to improve the program so that it can be more easily implemented by teachers and students by involving all school stake holders . The work arrangement for the Principal of Sunggal 1 Public Middle School is carried out by the principal by forming a school management team where the management section will formulate the main tasks and functions of each group in the school organizational structure by dividing tasks according to the existing school organizational structure. Supervision of the principal of SMP Negeri 1 Sunggal is carried out through two stages, namely direct supervision by going directly to the field and indirect supervision by requesting reports from school officials and involving supervision of other parties. Factors supporting the teaching performance of teachers at SMP Negeri 1 Sunggal come from within the school such as infrastructure, teachers and collaboration with all parties, then for supporting factors that come from outside the school, namely collaboration with Higher Education Institutions while inhibiting factors include lack of teacher competence, teaching methods teaching is monotonous, the budget is inadequate, the teacher's ability to use ICT is low plus there is an attitude of resignation due to the age factor to keep up with technology and information developments